Does a Patient-Managed Insulin Intensification Strategy With Insulin Glargine and Insulin Glulisine Provide Similar Glycemic Control as a Physician-Managed Strategy? Results of the START (Self-Titration With Apidra to Reach Target) Study: A Randomized Noninferiority Trial - HARRIS, Stewart B; YALE, Jean-François; BERARD, Lori; STEWART, John; ABBASZADEH, Babak; WEBSTER-BOGAERT, Susan; GERSTEIN, Hertzel C (Diabetes care, 2014)
OBJECTIVE Diabetes self-management is universally regarded as a foundation of diabetes care. We determined whether comparable glycemic control could be achieved by self-titration versus physician titration of a once-daily bolus insulin dose in patients with type 2 diabetes who are unable to achieve optimal glycemia control with a basal insulin. RESEARCH DESIGN AND METHODS Patients with type 2 diabetes, an HbA1c level >7% (53 mmol/mol), and either nocturnal hypoglycemia episodes or an insufficient basal insulin glargine level (with or without oral agents) to achieve a fasting plasma glucose level ≤6 mmol/L (108 mg/dL) were studied. Participants all had bolus insulin glulisine added at breakfast and were allocated to either algorithm-guided patient self-titration or physician titration. The primary outcome was an HbA1c level ≤7% (53 mmol/mol) without severe hypoglycemia. RESULTS After a mean (SD) follow-up of 159.4 days (36.2 days), 28.4% of participants in the self-titration arm vs. 21.2% in the physician titration arm achieved an HbA1c level of ≤7% (53 mmol/mol) without severe hypoglycemia (between-group absolute difference 7.2%; 95% CI -3.2 to 17.7). The lower end of this 95% confidence interval was within the predetermined noninferiority boundary of -5% (P noninferiority = 0.011). CONCLUSIONS In stable patients with type 2 diabetes who are receiving doses of basal insulin glargine who require bolus insulin, a simple bolus insulin patient-managed titration algorithm is as effective as a physician-managed algorithm.